2020
DOI: 10.1590/s1677-5538.ibju.2019.0360
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis accuracy of PCA3 level in patients with prostate cancer: a systematic review with meta-analysis

Abstract: Background: The diagnostic value and suitability of prostate cancer antigen 3 (PCA3) for the detection of prostate cancer (PCa) have been inconsistent in previous studies. Thus, the aim of the present meta-analysis was performed to systematically evaluate the diagnostic value of PCA3 for PCa. Materials and Methods: A meta-analysis was performed to search relevant studies using online databases EMBASE, PubMed and Web of Science published until February 1st, 2019. Ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 84 publications
(43 reference statements)
0
11
0
2
Order By: Relevance
“…[1] W dużej metaanalizie włączającej ponad 12 tysięcy pacjentów, czułość metody została określona na 65%, swoistość na 82%, przy NPV 90.0%. [1,12] PCA3 stał się także elementem kalkulatora ryzyka ERSPC, gdzie nieznacznie zwiększył detekcję raka prostaty (z 79% na 83%). [12] SelectMDx W badaniu SelectMDx mierzymy poziomy mRNA DLX1 i HOX6 w moczu po badaniu per rectum (DRE).…”
Section: Results and Conclusionunclassified
“…[1] W dużej metaanalizie włączającej ponad 12 tysięcy pacjentów, czułość metody została określona na 65%, swoistość na 82%, przy NPV 90.0%. [1,12] PCA3 stał się także elementem kalkulatora ryzyka ERSPC, gdzie nieznacznie zwiększył detekcję raka prostaty (z 79% na 83%). [12] SelectMDx W badaniu SelectMDx mierzymy poziomy mRNA DLX1 i HOX6 w moczu po badaniu per rectum (DRE).…”
Section: Results and Conclusionunclassified
“…LncRNA, a type of ncRNA with a transcript longer than 200 nt, does not encode proteins or only encodes short peptides ( 14 , 15 ) A large number of studies have revealed that lncRNA plays a non-negligible role in the development of PCa ( 21 , 22 ). Prostate cancer antigen 3 (PCA3), as one of the LncRNAs, has been proven to be a diagnostic marker to improve the diagnostic efficacy of PSA in PCa and has been approved by the FDA to guide repeated prostate biopsy ( 23 , 24 ). The lncRNA sequence contains nucleic acid binding sites and can be folded to form higher-level structures with corresponding protein-binding sites, which interacts with DNA, RNA, and proteins to affect the regulation of body functions ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of validated secondary oncomarkers, with improved specificity for PCa, appeared on the clinical scene and have already been included into American and European recommendations under the term “liquid biopsy”. Among them are such long non-coding urine-based mRNAs as Prostate Cancer Antigen 3 (PCA3) [ 4 ], HOXC6, DLX1 [ 5 ], and TMPRSS2-ERG (T2:ERG) [ 6 ], which are called on to help determine whether repeat puncture biopsy is needed after an initially negative biopsy. An example of a complex personalized approach to PCa risk calculation is incorporated into the Prostate Cancer Prevention Trial Risk Calculator patients’ clinical data, including levels of PSA, free PSA, and expression of PCA3 and T2:ERG.…”
Section: Genomics: Molecular Marker-based Personalized Approaches To Prostate Cancermentioning
confidence: 99%